2016
DOI: 10.5751/es-08156-210204
|View full text |Cite
|
Sign up to set email alerts
|

Building local institutions for national conservation programs: lessons for developing Reducing Emissions from Deforestation and Forest Degradation (REDD+) programs

Abstract: ABSTRACT. For programs that aim to promote forest conservation and poverty alleviation, such as Reducing Emissions from Deforestation and Forest Degradation (REDD+), the participation of indigenous communities is essential to meet program goals. Using Ostrom's theory of collective action for common pool resource management, we evaluated the institutions governing indigenous participation in the Programa Socio Bosque incentive-based conservation program in Ecuador. We conducted structured interviews with 94 mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…"Capacity to undertake such monitoring [of cobenefits] is very limited at present and so progress will depend on donor support for funding and for building up capacity" (Lao PDR 2010:84). This sparse consideration of community-based management and monitoring in the reports coincides with the realities that several studies found on the ground for these and other countries: the lack of a more nuanced policy approach that facilitates bottom-up institutional development for a stronger community involvement (Danielsen et al 2013, Collen et al 2016.…”
Section: Hierarchy Among Monitoring Practices In Complex Redd+ Governsupporting
confidence: 63%
“…"Capacity to undertake such monitoring [of cobenefits] is very limited at present and so progress will depend on donor support for funding and for building up capacity" (Lao PDR 2010:84). This sparse consideration of community-based management and monitoring in the reports coincides with the realities that several studies found on the ground for these and other countries: the lack of a more nuanced policy approach that facilitates bottom-up institutional development for a stronger community involvement (Danielsen et al 2013, Collen et al 2016.…”
Section: Hierarchy Among Monitoring Practices In Complex Redd+ Governsupporting
confidence: 63%
“…For effective participation of indigenous communities in REDD+ activities, rules need to be implemented at multiple levels (Collen et al 2016). Constitutional-level and collective choice rules are easier to establish relative to operational rules, which require regular execution and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a negative relation between the PCA compliance and the number of forest fires. The authors Loaiza et al (2016) and Collen et al (2016) addressed REDD+ efforts in different contexts. They used Ostrom's Principles (1990) to assess land configuration and institutional arrangements for decision-making on the use of shared resources and their 2 Retrieved publications by the first search classified in case studies (followed by the country/region where the study was conducted) and non-case studies.…”
Section: Case Studiesmentioning
confidence: 99%
“…ROMANELLI AND BOSCHI implications for REDD+ implementation. Collen et al (2016) adopted an approach on building local institutions to national conservation programs by highlighting lessons for the development of REDD+ programs. To date, payment schemes for environmental services (PES), aimed at preserving threatened tropical forests (often denoted as "reduced emissions from deforestation" and "forest degradation" -REDD+ schemes) have shown positive impacts on forestry net economy.…”
Section: Cernementioning
confidence: 99%